Signaling sarcasm: From hyperbole to hashtag. Issue 4 (July 2015) - Kunneman, Florian; Liebrecht, Christine; van Mulken, Margot; van den Bosch, Antal
Highlights The use of hashtags such as #sarcasm reduces the further use of linguistic markers of sarcasm in tweets. Hashtags such as #sarcasm appear to be the extralinguistic equivalent of non-verbal expressions in live interaction. Sarcastic hashtags are 90% appropriate. Sarcastic tweets without hashtags are hard to distinguish from non-sarcastic hyperbolic tweets. In French tweets, the hashtag #sarcasme conveys a polarity switch less frequently than in Dutch.